EFISIENSI TATANIAGA EKSPOR BIJI TENGKAWANG DARI KALIMANTAN BARAT - Satria Astana; Subandi Antaatmaja; Rachman Effendi; Buharman Buharman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Efficiency of marketing system has an important role in supply and demand balance. It could be indicated by the marketing margin. A lower marketing margin would mean lower prices to consumers, higher prices to producers, and a greater quantity of the good exchange.The marketing system for illipe-nuts export from West Kalimantan has two main channels, intermediate sellers and exporters. The price spread analysis reveals that the marketing system mechanism is inefficient. The farmer margin is 45.83% and the marketing margin is 54.17% of the export price. The marketing margin consists of 32.27% of profit (and risk) margin and 21.90% of marketing cost. The biggest marketing cost is on the intermediate seller (12.50%). However, the highest margin for profit (and risk) is on the exporter (19.76%); the margin for profit (and risk) for the intermediate seller is 12.5% and the marketing cost for the exporter is 9.40%..In the marketing system, the farmer's earning is 17.01% of the production cost when poor harvest; the production cost is Rp. 64276.38 includes 58.41% of accomodation costs, 35.99% of transportation costs and 5.60% of tool costs. In the rich harvest, the farmer's earning is estimated at 30.0% of the production cost under the assumption that the decreasing of the price due to the production increases is about 18%. If inefficiency of the marketing system can be overcomed, the farmer's earning both in the poor and rich harvests will be able to increase.